Three-dimensional simulation of performance in through-mask electrochemical micromachining. (December 2020) - Tsai, Te-Hui; Lin, Ming-Yuan; Fan, Zhi-Wen; Lin, Hung-Lin
Through-mask electrochemical micromachining (TMEMM) is a kind of microfabrication. The major feature of through-mask electrochemical micromachining is that the tool is not limited by the shape, and can be processed in various shapes according to the pattern on the mask. This paper uses the finite element method to create a three-dimensional model to discuss the influence of flow direction, voltage, and electrolyte flow rate on the shape of the through-mask electrochemical micromachining. The simulation results show that processing shape is deeply affected by processing parameters, electrolyte flow rate affects processing temperature distribution, and temperature distribution at the bottom of aperture affects processing depth and flatness during processing, which in turn causes the difference in orifice size and roundness. At the same flow rate, the larger voltage, the larger average radius, flatness, and roundness. At the same voltage, the faster flow rate, the lower average depth, flatness, and average radius. Overall, it has best-processed aperture profile at a flow rate of 0.5 m/s. As a whole, the through-mask electrochemical micromachining is indeed suitable for array microfabrication of various shapes. In this study, experiments were added to verify the simulation results. At a fixed electrolyte flow rate, when the voltage, concentration, and mask aperture are changed, it will have an effect on the overall experimental results. From the experimental results, we know that the electrolyte flow rate and temperature distribution will indeed affect the overall processability.